1977
DOI: 10.1136/thx.32.2.232
|View full text |Cite
|
Sign up to set email alerts
|

A conservative approach in selected cases of late diagnosed oesophageal perforation.

Abstract: . (1977). Thorax, 32,[232][233][234]. A conservative approach in selected cases of late diagnosed oesophageal perforation. A conservative method is presented for the treatment of oesophageal perforation where the diagnosis has been delayed. A system of tubes is described which allows the patient to be fed and at the same time prevents swallowed material from reaching the fistula. A case is reported which was successfully managed using the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Nonoperative management includes keeping the patient nil by mouth for 2–3 days, nasogastric tube, broad-spectrum antimicrobial therapy, total parenteral nutrition, and drainage of pleural or mediastinal collection by chest drain or CT guided catheters [ 39 , 40 ]. Although few cases have been reported successfully treated with endoscopically placed coated stents and clipping, their clear role yet needs to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Nonoperative management includes keeping the patient nil by mouth for 2–3 days, nasogastric tube, broad-spectrum antimicrobial therapy, total parenteral nutrition, and drainage of pleural or mediastinal collection by chest drain or CT guided catheters [ 39 , 40 ]. Although few cases have been reported successfully treated with endoscopically placed coated stents and clipping, their clear role yet needs to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the greater the delay in the diagnosis of perforation, the more edematous and necrotic is the esophageal wall. In this circumstance, identification of the esophageal wall can be extremely challenging during dissection and attempt at direct repair frequently fails [ 14 , 16 ]. We used this method in four patients, two with cervical and two with thoracic perforations.…”
Section: Discussionmentioning
confidence: 99%
“…Although esophageal resection is a major intervention, it is safe and reliable treatment option for complicated perforation of the thoracic esophagus. During the procedure, intrathoracic sepsis can be eliminated confidently, as its source, the leaking esophagus, is removed [ 14 , 16 ]. Primary esophageal resection is indicated in the following circumstances: concurrent obstructive esophageal disease is detected, the injury is relatively extensive and associated with mediastinal or intrapleural sepsis, the viability of the wound edges, principally the mucosa, is in doubt, primary over swing of the perforation would result in at least 50% narrowing of the esophageal lumen, and generalized sepsis has already developed [ 1 , 5 , 9 , 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have placed catheters under continuous suction via the nose into the mid-oesophagus and stomach, but have not been satisfied with the presence of tubes in the oropharynx and have found that these suction catheters often block and are difficult t o maintain. Verwoerd et al (6) partly overcame these problems by placing suction catheters in the oesophagus and stomach via a gastrostomy.…”
Section: Discussionmentioning
confidence: 99%